Patterns and effects of entry in US airline markets - Kai Hüschelrath; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We use T-100 traffic data and DB1B fare data from the U.S. Department of Transportation to identify patterns and effects of entry by network carriers and low-cost carriers in non-stop U.S. airline markets. For the sample period from 1996 to 2009, we find that entry activity of low-cost carriers did not only experience significant absolute increases but also led to substantial fare reductions. As route entries by network carriers do not have comparable effects, the existence and expansion of low-cost carriers must be considered as the main driver of competition in the domestic U.S. airline industry.
Keywords: L40; L93; 330; Airline industry; liberalisation; entry; low-cost carriers